2016
DOI: 10.4271/2016-01-0861
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analyses of Liquid and Spray Penetration under Heavy-Duty Diesel Engine Conditions

Abstract: The modeling of fuel sprays under well-characterized conditions relevant for heavy-duty Diesel engine applications, allows for detailed analyses of individual phenomena aimed at improving emission formation and fuel consumption. However, the complexity of a reacting fuel spray under heavy-duty conditions currently prohibits direct simulation. Using a systematic approach, we extrapolate available spray models to the desired conditions without inclusion of chemical reactions. For validation, experimental techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Experiments were conducted in an optically-accessible, highpressure, high-temperature, constant-volume vessel, capable of reaching ambient conditions characteristic for current generations of compression-ignition engines [27,28]. The ambient environment in the current study targets the Spray A condition of the Engine Combustion Network (ECN), with a local gas temperature of 900 K, oxygen concentration of 15 vol%, and a density of 22.8 kg/m 3 [26].…”
Section: Pre-burn Combustion Vessel and Injection Strategymentioning
confidence: 99%
“…Experiments were conducted in an optically-accessible, highpressure, high-temperature, constant-volume vessel, capable of reaching ambient conditions characteristic for current generations of compression-ignition engines [27,28]. The ambient environment in the current study targets the Spray A condition of the Engine Combustion Network (ECN), with a local gas temperature of 900 K, oxygen concentration of 15 vol%, and a density of 22.8 kg/m 3 [26].…”
Section: Pre-burn Combustion Vessel and Injection Strategymentioning
confidence: 99%
“…High-speed liquid-and vapor-phase fuel penetration were measured for non-reacting experiments using DBI and Schlieren, respectively. Further details about the employed optical techniques can be found here [20,27]. The experimental results reported in this work were constructed using ensemble averages of at least 10 individual recordings.…”
Section: Tu/e Combustion Vesselmentioning
confidence: 99%
“…To better predict the fuel-air mixing process, local refinement was used in the region where the spray evolves, where mesh size ranges from 0.3 to 1 mm. The spray model presented in this work was extensively validated in [20], where a suitable methodology for a consistent comparison between computed and DBI experimental data of liquid penetration was also developed. In particular, a light scattering model was implemented by the authors following the recent methods suggested by Magnotti and co-authors [21].…”
Section: Tu/e Combustion Vesselmentioning
confidence: 99%
See 2 more Smart Citations